Sebuah Analisis Terhadap Sosial Ekonomi di Kabupaten Aceh Barat Daya - Al Zikri; Rollis Juliansyah (Universitas 45 Surabaya, 2024)
Poverty is a condition in which a person or group of people does not have adequate access to the economic, social, and political resources necessary to meet basic needs. Southwest Aceh is one of the districts in Aceh, according to data obtained from BPS, the poverty rate in Southwest Aceh is still too high, reaching 15%. This study uses a descriptive quantitative method, the researcher chose this method to obtain an overview of how much the influence of education level, unemployment, minimum wage and population growth on poverty in Southwest Aceh Regency. The population in this study is all areas in Southwest Aceh Regency. As for the selection of samples, it uses saturated samples, which means that all populations are sampled, namely as many as 9 districts. This research data is sourced from data from the Central Statistics Agency (BPS) of Aceh Province, especially Southwest Aceh in the period 2010 to 2021. The type of data used is secondary data in the form of data on education levels, unemployment, minimum wage, population growth and poverty. The tests carried out include statistical tests such as multiple linear regression analysis, T test, and F test, determination coefficient. The results of the study stated that the level of education and population growth had no partial effect on poverty in Southwest Aceh. Meanwhile, unemployment and minimum wage have a partial influence on poverty in Southwest Aceh. Simultaneously, the level of education, unemployment, minimum wage and population growth have an influence on unemployment in Southwest Aceh. Education levels, unemployment, minimum wage and population growth have a great influence on poverty in Southwest Aceh.